دور الجامعات الفلسطينية في تحقيق المواطنة الرقمية لدى طلبتها في ظل تنامي التواصل الرقمي: جامعة الأقصى نموذجا - مغاري، أحمد محمد عبدالله (اتحاد الجامعات العربية - الأمانة العامة, 2023)
هدف المقال التعرف إلى دور جامعة الأقصى في تحقيق المواطنة الرقمية لدى طلبتها في ظل تنامي التواصل الرقمي. استخدمت الدراسة المنهج الوصفي، وطريقة المسح حيث تم تطبيق البحث على عينة قوامها (377) طالبا وطالبة في جامعة الأقصى. وتوصلت الدراسة إلى نتائج، من أهمها: يستخدم معظم الطلبة تكنولوجيا التواصل الرقمي كثيرا، وطوال الأسبوع، ولزمن يزيد على أربع ساعات. وتقوم الجامعة بدور متوسط في تحقيق المواطنة الرقمية لدى طلبتها. وتوجد فروق ذات دلالة إحصائية بين متوسط تقديرات الطلبة تبعا لمتغير النوع في مجالي الاحترام والتعليم، لصالح الطلاب. وتوجد فروق أيضا تبعا لمتغير المستوى الدراسي، في مجال التعليم، لصالح المستويين الأخيرين. وتوجد فروق تبعا لمتغير المعدل الدراسي لصالح مستويات المعدلات الأقل مقارنة بمستوى النسبة الأعلى. ولا توجد فروق تبعا لمتغير التخصص الدراسي. وقد أوصت الدراسة باستمرار دور الجامعة في تحقيق المواطنة الرقمية لدى طلبتها، وتطويره. ودمج المواطنة الرقمية في العملية التدريسية، والاهتمام بعقد الدورات والتعاون مع مؤسسات المجتمع في هذا الميدان. The article aimed to identify the role of Al-Aqsa University in achieving digital citizenship among its students in light of the growing digital communication. The study used a descriptive approach and the survey method, as the research was applied to a sample of (377) male & female students at Al-Aqsa University. The study reached results, the most important of which are: Most students use digital communication technology a lot throughout the week & for a period of more than four hours. The university plays a mediating role in achieving digital citizenship among its students. There are statistically significant differences between the students' average estimates according to the gender variable in the domains of respect & education in favor of the students. We also find differences, according to the academic level variable, in the field of education in favor of the last two levels. We find differences according to the academic average variable in favor of the lowest level compared to the highest rate level. There are no differences according to the academic specialization variable. The study recommended the continuation of the role of the university in achieving & developing digital citizenship among its students. Integration of digital citizenship in the teaching process, interest in holding courses & cooperation with community institutions in this field.
Keywords: التعليم الجامعي -- المواطنة الرقمية -- الاتصال الرقمي -- طلبة الجامعات -- جامعة الأقصى